Postmenopausal syndrome - Dalal, Pronob K. (Indian J Psychiatry, 2015)
Menopause is one of the most significant events in a woman's life and brings in a number of physiological changes that affect the life of a woman permanently. There have been a lot of speculations about the symptoms that appear before, during and after the onset of menopause. These symptoms constitute the postmenopausal syndrome; they are impairing to a great extent to the woman and management of these symptoms has become an important field of research lately. This chapter attempts to understand these symptoms, the underlying pathophysiology and the management options available.